Immunotherapy resistance in solid tumors: mechanisms and potential solutions - Daniel S. Lefler; Steven A. Manobianco; Babar Bashir (Cancer Biology & Therapy)
While the emergence of immunotherapies has fundamentally altered the management of solid tumors, cancers exploit many complex biological mechanisms that result in resistance to these agents. These encompass a broad range of cellular activities – from modification of traditional paradigms of immunity via antigen presentation and immunoregulation to metabolic modifications and manipulation of the tumor microenvironment. Intervening on these intricate processes may provide clinical benefit in patients with solid tumors by overcoming resistance to immunotherapies, which is why it has become an area of tremendous research interest with practice-changing implications. This review details the major ways cancers avoid both natural immunity and immunotherapies through primary (innate) and secondary (acquired) mechanisms of resistance, and it considers available and emerging therapeutic approaches to overcoming immunotherapy resistance.